Biodiversity Of Dragonflies In Petulu Village, Ubud District, Gianyar Regency, Bali - Dalem, Anak Agung Gde Raka; Subagyo, Job Nico; Suartini, Ni Made (Metamorfosa: Journal of Biological Sciences, 2022)
ABSTRACT Rearch on “Biodiversity of Dragonflies in Petulu Village, Ubud District, Gianyar Regency, Bali” was undertaken between May and October, 2020. Objectives of this research were  to find out species and biodiversity of dragonflies of Petulu Village.  Sample were collected from some research locations representing different habitats, such as rice fields, settlements, and plantations.  Dragonflies which were caught or sighted on research area whould be caught by insect nests when possible and then were brought to the laboratorium at Biology Department-Fmipa Udayana University, Bali for species identification.  Identification was conducted refering to some books and manuals, such as Wahyu Sigit Rhd (2013), Lilies S. (1992), etc. Data of dragonflies that were recorded including name of species and their relative abundances, and then the results were presented on a table.  The status of each species (protected or not), was also provided.  Shannon-Wiener diversity indexes were calculated.  Results of this research showed that there were 12 species of dragonflies found, namely: Crocothemis servilia, Pantala flavescens, Orthetrum Sabina, Neurothemis terminata, Diplacodes trivialis , Potamarcha congener , Neurothemis ramburii, Orthetrum chrysis, Ischnura senegalensis, Agriocnemis femina, Agrionoptera insignis, dan Agriocnemis pygmaea. All dragonflies species found here were not protected by law. Biodiversity index (H’) of dragonflies in Petulu Village was 1.63, which indicated condition of community structure of dragonflies in Petulu Village was stable within the category of moderate.   Keywords: Bali, biodiversity, dragonfly, identification, Petulu